Dilemmas in Endoscopic Management of Rectal Neuroendocrine Tumors: A Case-Based Discussion - Brian P. Rajca; Mihir S. Wagh (Gastroenterology Research and Practice)
Rectal neuroendocrine tumors are uncommon neoplasms that historically were regarded as having an indolent course. Due to the widespread use of screening colonoscopy neuroendocrine tumors of the rectum are identified with increasing frequency. More recent literature has suggested that rectal neuroendocrine tumors may progress in a more malignant fashion than previously believed. In this case-based discussion we present management dilemmas, analyze current guidelines, and highlight the role of endoscopic ultrasound, endoscopic resection, and surgery.